Optimum Design for Mechanical Structures and Material Properties of the Dual-Elbow-Bar Mechanism - Weiguo Lin; Chen Zhou; Weijun Huang (Advances in Materials Science and Engineering)
According to the kinematic equation of the die-cutting machine with the dual-elbow-bar mechanism, the angular acceleration curve figure can be obtained exactly through the analysis of MATLAB program when the die-cutting machine runs at the highest speed (6000 r/h). The material properties of the cam driving mechanism are analyzed by QFD (Quality Function Deployment) method, and the optimum design project is presented based on conjugate cam driving mechanism. The reverse design and the outline of conjugate cam mechanism are obtained by MATLAB program. The kinematical form of optimized design conjugate cam driving mechanism is simulated and analyzed by ADAMS software. The results show that the optimum design mechanism could raise the highest speed of the die-cutting machine up to 7500 r/h and improve the overall performance of the machine.